Social relationships and trust - Christine Binzel; Dietmar Fehr (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
While social relationships play an important role for individuals to cope with missing market institutions, they also limit individuals' range of trading partners. This paper aims at understanding the determinants of trust at various social distances when information asymmetries are present. Among participants from an informal housing area in Cairo we find that the increase in trust following a reduction in social distance comes from the fact that trustors are much more inclined to follow their beliefs when interacting with their friend. When interacting with an ex-ante unknown agent instead, the decision to trust is mainly driven by social preferences. Nevertheless, trustors underestimate their friend's intrinsic motivation to cooperate, leading to a loss in social welfare. We relate this to the agents' inability to signal their trustworthiness in an environment characterized by strong social norms.
Keywords: C72; C93; D82; O12; 330; trust; hidden action; social distance; solidarity; reciprocity; economic development; Soziale Beziehungen; Vertrauen; Austauschtheorie; Asymmetrische Information; Theorie; Informeller Sektor; Kairo